1994
DOI: 10.1002/bjs.1800811033
|View full text |Cite
|
Sign up to set email alerts
|

Plasma elastase in venous disease

Abstract: The plasma elastase level was measured as a marker of neutrophil degranulation in three groups, each of 15 patients, with uncomplicated varicose veins, lipodermatosclerosis (LDS) and venous ulceration. The values obtained were compared with those in age- and sex-matched control subjects. Significantly higher levels of elastase were found in all patient groups compared with controls: median 25.6 ng/ml for patients with uncomplicated varicose veins, 22.1 ng/ml for those with LDS, 26.0 ng/ml for those with venous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 30 publications
3
27
1
Order By: Relevance
“…In our earlier work [35, 36, 37, 38, 39, 40, 41], we found evidence of leucocyte activation and raised levels of endothelial adhesion molecules. The most likely explanation for these observations is that venous disease is associated with a systemic inflammatory response and a pro-inflammatory state of the endothelium.…”
Section: Implications For Pharmacological Treatment In Venous Diseasesupporting
confidence: 53%
See 1 more Smart Citation
“…In our earlier work [35, 36, 37, 38, 39, 40, 41], we found evidence of leucocyte activation and raised levels of endothelial adhesion molecules. The most likely explanation for these observations is that venous disease is associated with a systemic inflammatory response and a pro-inflammatory state of the endothelium.…”
Section: Implications For Pharmacological Treatment In Venous Diseasesupporting
confidence: 53%
“…Blood was taken from the arm veins of patients (not the lower limb veins) of patients with varicose veins, liposclerotic skin change and active venous ulceration [39, 40]. In each group, the median level of lactoferrin and elastase was higher in the patients than in the age- and sex-matched controls (fig.…”
Section: Leucocyte Activationmentioning
confidence: 99%
“…There is no mention in the literature of these PMN parameters in this clinical condition. It is believed that the behavior of the cytosolic Ca 2+ concentration of PMN cells in these patients might express the basal activation of granulocytes [26][27][28][29], although confirmation comes from studies evaluating the plasma elastase [8] and lactoferrin levels [7] observed in this clinical condition.…”
Section: Discussionmentioning
confidence: 99%
“…As is well known, the role played by leukocytes in the microcirculation of subjects with chronic venous hypertension is diverse and in fact, while trapping especially concerns monocytes, activation involves granulocytes [13]. An increase in lactoferrin level has also been demonstrated during acute experimental venous hypertension in normal subjects [7] and increased plasma elastase levels have also been found in subjects with some venous diseases, although this increase was not dependent on granulocyte count [8].…”
Section: Introductionmentioning
confidence: 99%
“…Under chronic conditions of venous pressure elevation, a number of indicators of inflammation can be detected (7,23), including endothelial adhesion molecule expression (22), release of proteolytic enzymes (26), and the presence of leukocyte migration into valve tissue and the venous wall (19,25). The trigger mechanisms that lead to development of the inflammatory reaction in venules with leukocyte and endothelial activation remain incompletely defined.…”
mentioning
confidence: 99%